Characteristic of the Source’s Base of the Researches of the Development of the Information Technologies Receiving in the Pedagogical Researches in Ukraine in the Second Half of XX at the Beginning of XXI Century and Method of its Formation - Olha Didenko (Pedagogical Discourse, 2013)
The article discovered the characteristic of the source’s base of the historical and pedagogical researches of the development of the primary information technologies receiving, described by Ukrainian scientists in their dissertations on study theories (didactics), theory of education and theory of management of the educational institutions, which were defended during 1950s - 2000s. Was developed the methodology of formation of base of the authentic sources (dissertations to the degree of Candidate of Pedagogical Sciences or Doctor of Pedagogical Sciences) with the help of combination of the method of the main array and selective method, stratified and  expert selection of determination their sufficient quantity which would ensure the completeness and reliability of the received results in the result of researching.